An approach for developing a tailored implementation intervention to implement a web-based application for men’s health screening in a primary care setting during the Covid-19 pandemic - Ooi, Chor Yau (2023)
A systematic review reported that tailoring implementation strategies to address the determinants of practice is effective. In this study, we propose an approach to develop a package of tailored strategies to implement a web-based application (ScreenMen) for men’s health screening in Kuala Lumpur, Malaysia. The tailored implementation intervention was developed using the following steps. Step 1: Brainstorming session-a panel of experts brainstormed to come up with as many approaches as possible to address the determinants, Step 2: Mapping of the approaches to implementation strategies-the approaches from the brainstorming session were mapped to implementation strategies from the Expert Recommendations for Implementing Change (ERIC) which is a compilation of 73 discrete implementation strategies from literature, Step 3: Selection of implementation strategies-implementation strategies were selected based on discussion with experts in primary care and implementation science and the context of the implementation site, Step 4: Specification of implementation strategies-selected implementation strategies were specified according to seven dimensions: actor, the action, action targets, temporality, dose, implementation outcomes addressed, and theoretical justification, Step 5: Modification of implementation strategies due to the Covid-19 pandemic-implementation strategies were evaluated using the APEASE (Affordability, Practicability, Effectiveness and cost-effectiveness, Acceptability, Side-effects/safety, Equity) criteria to decide on its feasibility due to restrictions on research activity during the pandemic and Step 6: Finalized tailored implementation intervention-implementation strategies that were accepted after evaluation with the APEASE criteria were included in the finalized tailored implementation intervention. A total of 58 approaches were generated and mapped to ERIC strategies. Subsequently, we selected 9 strategies based on their appropriateness and feasibility: involve executive boards, mandate change, provide education and training, create new clinical teams, identify and prepare champions, the use of information and technology, remind clinician, audit and provide feedback, and alter incentives/allowance structures. Following the evaluation using APEASE criteria, we removed 3 implementation strategies. The final tailored implementation intervention consisted of 6 implementation strategies: involve executive boards, mandate change, provide education and training, identify and prepare champions, use of information and communication technology, and audit and provide feedback. Using a systematic method enabled the development of a tailored implementation intervention to implement a web-based application for screening, even during a pandemic.